A Hypothalamic Leptin-Glutamate Interaction in the Regulation of Sympathetic Nerve Activity - Hong Zheng; Xuefei Liu; Yulong Li; Kaushik P. Patel (Neural Plasticity)
Accumulated evidence indicates that obesity-induced type 2 diabetes (T2D) is associated with enhanced sympathetic activation. The present study was conducted to investigate the role for leptin-glutamate signaling within the hypothalamus in regulating sympathetic nerve activity. In anesthetized rats, microinjections of leptin (5 ng ~ 100 ng) into the arcuate nucleus (ARCN) and paraventricular nucleus (PVN) induced increases in renal sympathetic nerve activity (RSNA), blood pressure (BP), and heart rate (HR). Prior microinjections of NMDA receptor antagonist AP5 (16 pmol) into the ARCN or PVN reduced leptin-induced increases in RSNA, BP, and HR in both ARCN and PVN. Knockdown of a leptin receptor with siRNA inhibited NMDA-induced increases in RSNA, BP, and HR in the ARCN but not in the PVN. Confocal calcium imaging in the neuronal NG108 and astrocytic C6 cells demonstrated that preincubation with leptin induced an increase in intracellular calcium green fluorescence when the cells were challenged with glutamate. In high-fat diet and low-dose streptozotocin-induced T2D rats, we found that leptin receptor and NMDA NR1 receptor expressions in the ARCN and PVN were significantly increased. In conclusion, these studies provide evidence that within the hypothalamic nuclei, leptin-glutamate signaling regulates the sympathetic activation. This may contribute to the sympathoexcitation commonly observed in obesity-related T2D.